Creative nonfiction a manual for Filipino writers - Hidalgo, Cristina Pantoja (University of the Philippines Press, 2003)
Contents: Creative nonfiction in the Philippines. Strategies of creative nonfiction writings. Types of creative nonfiction. Short concluding chapter.